Трудоресурсный потенциал Беларуси: совершенствование региональной политики - Сидорович, А. А. (Культура народов Причерноморья, 2014)
В статье на примере Республики Беларусь рассматривается методика экономикогеографического исследования трудоресурсного потенциала для обоснования территориальнодифференцированной региональной политики. Данная методика включает 4 этапа: разработка типологии административных районов по характеру воспроизводства трудоресурсного потенциала; выбор «ключевых» районов; проведение SWOT-анализа их развития; разработка направлений оптимизации территориальной организации трудоресурсного потенциала. У статті на прикладі Республіки Білорусь розглядається методика економіко-географічного дослідження трудоресурсного потенціалу з метою обґрунтування територіально-диференційованої регіональної політики. Зазначена методика включає 4 етапи: розробка типології адміністративних районів за характером відтворення трудоресурсного потенціалу; вибір «ключових» районів; проведення SWOT-аналізу їхнього розвитку; розробка напрямків оптимізації територіальної організації трудоресурсного потенціалу. The article describes the technique of economic and geographical study of Belorussian labor potential to support geographically differentiated regional policy. This technique includes four stages: elaboration typology of administrative regions in reproductive nature of labor resource; selection of key areas; performing of a SWOT-analysis of them; development of directions of optimization of the territorial organization of labor resource. The offered methods of economic-geographical study of LBP on the micro-geographical level, based on the usage of typological approach, cluster analysis, and SWOT-analysis provides improvement of the general methods of regional policy development, directed on optimization of the territorial LBP organization. The conducted analysis based upon these methods allowed establishing that each third region of Belarus is characterized by extremely unbalanced state of LBP reproduction. The results of the conducted SWOT-analysis for typical administrative regions of Belarus, which allow determination of their strong and weak sides, advantages and threats, were lied in the basis of development of the directions on optimization of the demographic population employment development, and LBP development. As a result of synthesis and systematization of the theoretic and methodological approaches of the above-stated researchers to studying LBP, the methods of economic-geographic study for substantiation of the territorialdifferentiated regional policy, based upon usage of the traditional geographic methods, adaptation of the modern economic methods and methods of multi-dimensional statistics were improved. Keywords: labor potential, Belarus, regional policy, typology, the method of keys, SWOT-analysis.